HIV and hepatitis C virus coinfection in Canada: challenges and opportunities for reducing preventable morbidity and mortality. Issue 1 (28th May 2012) - Klein, MB; Rollet, KC; Saeed, S; Cox, J; Potter, M; Cohen, J; Conway, B; Cooper, C; Côté, P; Gill, J; Haase, D; Haider, S; et al.
Abstract : Objectives: Hepatitis C virus (HCV) has emerged as an important health problem in the era of effective HIV treatment. However, very few data exist on the health status and disease burden of HIV/HCV‐coinfected Canadians. Methods: HIV/HCV‐coinfected patients were enrolled prospectively in a multicentre cohort from 16 centres across Canada between 2003 and 2010 and followed every 6 months. We determined rates of a first liver fibrosis or endstage liver disease (ESLD) event and all‐cause mortality since cohort enrolment and calculated standardized mortality ratios compared with the general Canadian population. Results: A total of 955 participants were enrolled in the study and followed for a median of 1.4 (interquartile range 0.5–2.3) years. Most were male (73%) with a median age of 44.5 years; 13% self‐identified as aboriginal. There were high levels of current injecting drug and alcohol use and poverty. Observed event rates [per 100 person‐years; 95% confidence interval (CI)] were: significant fibrosis (10.21; 8.49, 12.19), ESLD (3.16; 2.32, 4.20) and death (3.72; 2.86, 4.77). The overall standardized mortality ratio was 17.08 (95% CI 12.83, 21.34); 12.80 (95% CI 9.10, 16.50) for male patients and 28.74 (95% CI 14.66, 42.83) for female patients. The primary causes of death were ESLD (29%) and overdose (24%). Conclusions: We observed excessive morbidity and mortality in this HIV/HCV‐coinfected population in care. Over 50% of observed deaths may have been preventable. Interventions aimed at improving social circumstances, reducing harm from drug and alcohol use and increasing the delivery of HCV treatment in particular will be necessary to reduce adverse health outcomes among HIV/HCV‐coinfected persons.